Comparative Efficacy of Low-Dose Ketamine versus Midazolam Co-induction on Hemodynamic Stability and Early Neurocognitive Recovery in Geriatric Anesthesia: A Randomized Double-Blind Pilot Trial - Aditya Guna Wicaksono Panatagama; Aswoco Andyk Asmoro; Arie Zainul Fatoni; Rudy Vitraludyono (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Geriatric patients undergoing general anesthesia are susceptible to hemodynamic instability and delayed neurocognitive recovery. The choice of co-induction agent significantly influences these outcomes. This study compares the effects of low-dose Ketamine versus Midazolam co-induction on intraoperative hemodynamic stability and immediate post-operative cognitive trajectory. Methods: A prospective, double-blind, randomized controlled pilot trial was conducted on 32 geriatric patients aged 65 years or older classified as American Society of Anesthesiologists (ASA) physical status II or III undergoing elective surgery. Patients were randomized to receive either intravenous Ketamine (0.3 mg/kg, n=16) or Midazolam (0.075 mg/kg, n=16) prior to Propofol induction. The primary outcome was the magnitude of early cognitive change measured by the Mini-Mental State Examination (MMSE) at 1-hour post-operation relative to baseline. Secondary outcomes included intraoperative mean arterial pressure (MAP), incidence of hypotension, total Propofol consumption, and time to extubation. Data were analyzed using Analysis of Covariance (ANCOVA) and independent t-tests; effect sizes were calculated using Cohen’s d. Results: Baseline characteristics were comparable between groups. The Ketamine group exhibited significantly superior early cognitive preservation with a mean decline of -0.50 ± 0.63 compared to the Midazolam group, which showed a decline of -1.25 ± 0.93 (p = 0.012; Cohen’s d = 0.93). Hemodynamically, the Ketamine group maintained significantly higher Mean Arterial Pressure post-induction (p = 0.003) with a lower risk of hypotension (Relative Risk 0.29, 95% Confidence Interval 0.07–1.18). Additionally, the Ketamine group required significantly less induction of Propofol (p < 0.001) and achieved faster extubation times (p < 0.001). Conclusion: Co-induction with sub-anesthetic Ketamine provides superior hemodynamic stability and facilitates faster early neurocognitive recovery compared to Midazolam in geriatric patients. These findings suggest Ketamine is a preferable adjuvant for optimizing emergence profiles and maintaining perfusion pressure in the aging population.